The Real-Time-Score: Nucleus and Fluid Opus. - Winkler, GerhardE. (Contemporary Music Review, 2010)
The author describes his concept of Real-Time-Score, which he has used in compositions since 1994. Real-Time-Scores are based on the evolution of complex dynamic systems and generate the formal structure of an entire piece, which includes the following levels: the live sound played by the musician; the ad hoc electronically transformed live sound; and the interaction between the player and the computer. These aspects define a kind of musical self-organization, where the formal structure of a piece is unique to each performance as a result of the above-mentioned complex interrelations.